Anti-Ro/SSA antibodies in adult arrhythmias: pathogenesis, clinical implications, and therapeutic strategies - Cao, Ruotong; Lv, Huasheng; Tang, Baopeng; Lu, Yanmei (Frontiers in Immunology, 2025)
Anti-Ro/SSA antibodies, prevalent autoantibodies in connective tissue diseases, have well-established roles in fetal arrhythmias but their significance in adult arrhythmias remains underrecognized. Recent evidence highlights that anti-Ro/SSA antibodies may induce adult arrhythmias by disrupting cardiac ion channel function, particularly through interactions with calcium and potassium channels, leading to electrophysiological disturbances including QT prolongation, atrioventricular block, and increased susceptibility to sudden cardiac death. Additionally, these antibodies can initiate inflammatory cascades, further contributing to myocardial fibrosis and conduction abnormalities. Despite the growing clinical relevance, detection of anti-Ro/SSA antibodies in unexplained arrhythmias is not routinely performed, limiting early recognition and intervention. Therapeutic strategies, currently based primarily on immunomodulatory therapies, show promise yet lack definitive evidence from randomized controlled trials. This review systematically summarizes recent advances regarding the pathogenic mechanisms, clinical implications, and therapeutic strategies for anti-Ro/SSA antibody-associated adult arrhythmias, aiming to enhance awareness, diagnostic precision, and management of this increasingly recognized clinical entity.